2006
DOI: 10.1039/b606816b
|View full text |Cite
|
Sign up to set email alerts
|

Birch bark research and development

Abstract: This review will detail progress made in the previous decade on the chemistry and bioactivity of birch bark extractive products. Current and future applications of birch bark natural products in pharmaceuticals, cosmetics, and dietary supplements for the prevention and treatment of cancer, HIV,and other human pathogens are reviewed. Current developments in the technology of birch bark processing are discussed. New approaches for the synthesis of potentially valuable birch bark triterpenoid derivatives are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
177
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(181 citation statements)
references
References 220 publications
(175 reference statements)
3
177
0
1
Order By: Relevance
“…IR spectra were obtained using a JASCO FT/IR-420 spectrophotometer. NMR spectra were recorder on a Bruker Digital NMR-Avance 300 apparatus and on a Bruker Digital NMR-Avance 400 apparatus in CDCl 3 (5). To a solution of compound 2 (150 mg, 0.33 mmol) and anhydrous K 2 CO 3 (115 mg, 0.83 mmol) in dry DMF (2 ml) was added methyl iodide (41 ll, 0.66 mmol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra were obtained using a JASCO FT/IR-420 spectrophotometer. NMR spectra were recorder on a Bruker Digital NMR-Avance 300 apparatus and on a Bruker Digital NMR-Avance 400 apparatus in CDCl 3 (5). To a solution of compound 2 (150 mg, 0.33 mmol) and anhydrous K 2 CO 3 (115 mg, 0.83 mmol) in dry DMF (2 ml) was added methyl iodide (41 ll, 0.66 mmol).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Betulin 1 is a main component of birch bark, 3 and can be synthetically converted to betulinic acid 2 in a two-step procedure, in high yield. 4 Both 1 and 2 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our continuing study of the chief phytotherapeutic components of traditional Chinese medicines (TCM), [17][18][19] the phytochemical investigation on the seeds of Z. mauritiana was carried on. This led to the isolation of 11 spinosin derivatives (1-11), along with 11 other known compounds (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Compounds 1-3 are new acylated flavonoid C-glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopepeptide, 1,[7][8][9][10][11][12] triterpenes, 1 flavones, 1 steroids, 1,13 and aliphatic compounds 1,14 have previously been identified from the roots, barks and leaves of Z. mauritiana. Interestingly, some of these compounds showed antitumor, anti-HIV, 15,16 anti-plasmodial and anti-mycobacterial activities. 12 However, no chemical study was reported on the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Higher density provides better pulp yields, but decay is detrimental to both the pulping process and the pulp quality (Tammisola et al 1995). Trunks are debarked before pulping, but on the other hand, the content and properties of bark can be interesting also in terms of bioactive extracts, such as betulin, with beneficial pharmacological effects (Alakurtti et al 2006;Krasutsky 2006). In general, interest in the different chemical properties of bark and wood is increasing in the industries (Verkasalo et al 2017).…”
Section: Introductionmentioning
confidence: 99%